Solvent-free coumarin synthesis via pechmann reaction using solid catalysts - Kalita, Pranjal; Kumar, Rajiv (Microporous and Mesoporous Materials, 2012)
A solvent-free versatile and efficient methodology, reported here, allows the synthesis of coumarin by hydroxyalkylation of phenols with ethyl or methyl acetoacetate (via Pechmann reaction) using trifluoromethanesulfonic acid (trifle acid) functionalised Zr-TMS (Zr-TMS, zirconia based transition metal oxide mesoporous molecular sieves) catalysts with different loadings of triflic acid over Zr-TMS (5-25 wt.%) where the total acid strength of acid functionalised Zr-TMS material is increased as increasing loading of triflic acid from 5 to 25 wt.% leading to correspond increased higher catalytic activity. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Coumarin; Ethyl acetoacetate; Functionalization; Pechmann reaction; Resorcinol; Zr-TMS